Heparin Effect on Bone Density - Ginsberg, J S; Kowalchuk, G; Hirsh, J; Brill-Edwards, P; Burrows, R; Coates, G; Webber, C (Thrombosis and Haemostasis, 1990)
In order to provide estimates of the risks of symptomatic osteoporosis and reduced bone density in premenopausal women treated with long-term (greater than 1 month) heparin therapy, we evaluated a cohort of 61 consecutive premenopausal women previously treated with long-term heparin (cases) and a group of controls matched for age, parity and duration between the last pregnancy and evaluation. All patients underwent dual photon absorptiometry of the lumbar spine and single photon absorptiometry of the wrist and most cases underwent plain lateral radiography of the thoracolumbar spine in order to exclude silent fractures. Although none of the cases suffered symptomatic fractures (0 of 61, 95% confidence intervals 0.0 to 5.9%), there was a significantly greater proportion of cases than controls with bone density below our pre-defined levels. The long-term implications of our findings are uncertain but because it is possible that the reduction in bone density predisposes women to fractures, this potential risk should be considered when treating women with long-term heparin.